Commercial rehabilitation of the bankrupt A comparative study - Musa, Assistant teacher Ali Fadalah (The college of law and political science journal, 2023)
If the merchant does not announce it, its effects will have its effects with the creditors, and the effect of the debtor, and one of the most important effects in the commercial field is that returning the commercial consideration to the bankrupt erases all its effects. Ruling on the bankruptcy of the merchant or the commercial company, especially the one who wants it and the professional, until he regains the commercial and societal position he enjoyed before his bankruptcy, before bankruptcy , commercial rehabilitation is like penal rehabilitation according to what is decided by the law , whether commercial or criminal . When the merchant declares bankruptcy , it becomes as if he has committed a crime punishable by law , since in this case the creditor becomes a debtor to others , and he must pay the debts incurred by him, otherwise the court will order him to seize movable and immovable funds to pay off the debts he owes .If the bankruptcy end , this bankrupt merchant returne to his normal life , recovers his position in society , opens the door to repentance before him , gets rid of the stigma that befell him , resumes his business , and enjoys his rights and privileges , whether professional or political . This is what we will try to show in our research .